Assessment of local land and water institutions in the Blue Nile and their impact on environmental management - Hagos, Fitsum; Haileslassie, Amare; Awulachew, Seleshi Bekele (2009)
Land and water institutions play a vital role in managing and sustaining land and water resources as well as enhancing economic development and poverty alleviation efforts. While a lot has been done in terms of understanding the micro-determinants of farmers? decisions in land and water conservation, there is little attempt to understand the broad macro-institutional and organizational issues that influence land and water management decisions. The objective of the study was to assess institutional arrangements and challenges for improved land and water management in the Ethiopian part of the Blue Nile Basin (Tana and Beles subbasins). Focus group discussions and key informant interviews were held in Amhara and Benishangul Gumuz regions with important stakeholders such as the bureaus of Agriculture and Rural Development, Water Resources Development, Environmental Protection and Land Use Administration (EPLUA), National Agricultural Research Systems, and important NGOs, operating in the area of land and water management, and selected community members. As the major findings in this study, we outlined major land and water-related institutional arrangements that are currently in place and their design features, in order to identify those institutions related to superior performance. We highlighted major institutional and policy gaps and actions that are required to respond to emerging issues of environmental degradation, upstream/downstream linkages and climate change. Such analysis of institutions and their design features provides useful insights and contributes to the debate on institutional reform for improved land and water management in the Blue Nile Basin, in general. By doing so, it identifies the gaps in institutional arrangements and policies and potential remedies.